A catalogue of Hydryphantoidea from South America, with information on their geographic distribution and a key to families, subfamilies, genera, subgenera and species - de Castro, Luiz A. S. [UNESP]; Goldschmidt, Tom; Proctor, Heather C.; Ramírezsánchez, Marcia M.; Lofego, Antonio C. [UNESP] (My University, 2023)
The Cautín river is closely related to the economic development of Temuco city, Chile, and this river has along its course different kinds of human intervention. The present study aims to characterise the benthonic macroinvertebrate communities using species co-occurrence and niche sharing null models to understand the presence of a random or structured pattern in species assemblages for ten stations throughout the main course of the Cautín river from its origin to its low zones. The results of co-occurrence null model revealed that species associations are structured in one of three models, whereas two models revealed that species associations are random, whereas the results of the niche sharing null model revealed the absence of niche sharing, which would indicate the lack of interspecific competition. The obtained results provide information about the ecological structure and function in the benthos of the Cautín river, which would be similar to other descriptions for other Argentinean and Chilean Patagonian rivers.